2021
DOI: 10.1007/s11126-021-09955-2
|View full text |Cite
|
Sign up to set email alerts
|

The Psychiatric Burden on Medical Students in New York City Entering Clinical Clerkships During the COVID-19 Pandemic

Abstract: For medical students first entering the clinical space in July 2020, the unique challenges related to the coronavirus pandemic threatened to amplify the psychological distress associated with clerkship rotations. This study aimed to characterize the mental health of thirdyear medical students starting clinical clerkships in the midst of a pandemic by assessing symptoms of major depressive disorder (MDD), generalized anxiety disorder (GAD), and posttraumatic stress disorder (PTSD) as well as risk, coping, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…We argue that these results give a meaningful insight of the actual impact of the pandemic on medical students’ mental health as the two timepoints of the repeated cross-sectional study are highly comparable since they possibly share the same sociocultural features and, in addition, many mental health-associated variables were recorded in both timepoints, thus giving further substantial evidence to the findings of the review conducted by Mittal and colleagues [ 17 ]. Furthermore, the other variables that resulted significant in the models of Study 2 were mainly the same that the ones commented above (i.e., family cohesion, sexual orientation, economic situation, judgment of medical school choice) and also female gender, consistently with depression epidemiology [ 50 ] and with data on medical students’ stress [ 5 ], and relationships with peers, as shown in other studies on medical students both before and during the pandemic [ 21 , 40 ]. In addition, attending the last year of medical school reduced the risk of symptoms.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We argue that these results give a meaningful insight of the actual impact of the pandemic on medical students’ mental health as the two timepoints of the repeated cross-sectional study are highly comparable since they possibly share the same sociocultural features and, in addition, many mental health-associated variables were recorded in both timepoints, thus giving further substantial evidence to the findings of the review conducted by Mittal and colleagues [ 17 ]. Furthermore, the other variables that resulted significant in the models of Study 2 were mainly the same that the ones commented above (i.e., family cohesion, sexual orientation, economic situation, judgment of medical school choice) and also female gender, consistently with depression epidemiology [ 50 ] and with data on medical students’ stress [ 5 ], and relationships with peers, as shown in other studies on medical students both before and during the pandemic [ 21 , 40 ]. In addition, attending the last year of medical school reduced the risk of symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, available reviews about mental health among medical students during the pandemic have highlighted high levels of depression, anxiety, stress, and exhaustion, suggesting a rise in those symptoms [ 17 , 18 ]. However, most of studies had a cross-sectional [ 17 ] or a longitudinal design [ 19 , 20 , 21 ] without taking into account pre-pandemic periods, thus not allowing inferring about an actual worsening of mental health conditions compared with pre-pandemic years. To date, very few studies focusing on medical students have presented prospective (repeated cross-sectional or longitudinal) data beginning from a pre-pandemic period [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a study which found that psychological burden was higher with students having avoidant coping styles. [14,26] GAD-7 scores were significantly higher in participants who had themselves suffered or had experienced their family members or relatives suffering or dying from COVID-19. [15,21] Substance use and presence of comorbidities were not significantly associated with psychological distress, contradicted by earlier studies.…”
Section: Discussionmentioning
confidence: 89%
“…[15] Fear of COVID-19 was neither significantly impacted by any of the socio-demographic correlates nor by academic course, compliant with other studies. [26] This is most likely because of the time elapsed since start of the pandemic. The decrease in number of hospitalizations, deaths due to COVID-19 and pan-India vaccination might have helped in allaying fear of getting infected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation